Perception of Junior High School Students in Using iPusnas App as Medium for Increase Literacy Social Studies Subject - Aprizal Rama Hendrayanto; M. Muktiarni; Jonah Mupita (Universitas Pendidikan Indonesia (UPI), 2022)
The use of the iPusnas App as a medium of reading book has not been optimized by Indonesian students. The purpose of this research is to perceive about middle school students perseption on using iPusnas App in adding textbooks for social studies subject matter. This research will result in an update of: (1) Find out social studies secondary textbooks efficiently and (2) Adding textbooks sources to support social studies learning. The method used in this research is qualitative descriptive. This research method is carried out by distributing questionnaires, pos test and pre test, analyze, and describe the result. These results are expected to improve literacy by using iPusnas App as a medium of reading textbooks for social studies learning in addition to using texbooks provided by the school. The conclusion is students will find it easy to acces social studies textbooks anywhere and anytime with internet and iPusnas App and increase interest in literacy to students.